Mocking Others, Parodying Ourselves: Chants and Songs Used in Swedish Football - Herd, Katarzyna; Löfgren, Jakob (MUSICultures, 2020)
This article’s aim is to investigate the creative use of parody and sense-/nonsense-making visible in the Swedish football scene by looking into football chants through the lens of parody. The three examples selected (a song, a chant, and a music video) give a glimpse of possible folkloristic investigations in that context, as possibilities to work on varied and extensive material are profound. Theoretically, the article’s argument builds on Susan Stewart’s notion of sense and nonsense as connected, ongoing practices that structure our understanding of the world. The intertextual maze of chants is exemplified by musical creations from Swedish football clubs.